Integrating Qur’an and Science: Epistemology of Tafsir Ilmi in Indonesia - Akhmad Supriadi (Refleksi, 2017)
This paper describes four (4) types of epistemology on tafsir ‘ilmi (science exegesis) in Indonesia, which four experts have explained their own epistemology and its relation between Al-Qur’an and science, are Nazwar Syamsu, Achmad Baiquni, Muhammad Quraish Shihab and Agus Purwanto. These experts are selected as subject of research based on an opinion if they respectively have represent their own epistemology which differs each other. Based on the result of study and analysis, although all are working to integrate Al-Qur’an and science, these four experts have different epistemic reasoning to understand and explain a relation among Qur’anic verses on science. Nazwar Syamsu’s epistemology tends to an Islamization or Qur’anization of Qur’anic verses on science so its interpretation which is sourced from Al-Qur’an and scientific theory tends to look for Qur’anic justification through scientific theory. Type of epistemology which is initiated by Achmad Baiquni tends to dialogue between Al-Qur’an and modern scientific theory, so it will result unapologetical Islamic science but integrative-interconnective. The type of epistemology initiated by Achmad Baiquni has a similarity with Agus Purwanto’s, while Agus works to elaborate his own epistemology of Islamic science. He puts Al-Qur’an ashypothesis base, not Islamization nor Qur’anization of Qur’anic verses on science. Muhammad Quraish Shihab with his background as expert mufassir (Al-Qur’an interpreter) presents Al-Qur’an as Islamic miracle holy book through identification of modern Qur’anic verses on science. Even if on the one side it seems apologetic, but science exegesis of Quraish Shihab has different way of interpretation, he puts the scientific verses into function as medium to know God’s Greatness and take lessons from each phenomena which is relevant to modern science.